Menuju Lingkungan Berkelanjutan: Peningkatan Pemahaman Masyarakat Tentang Pentingnya Persiapan dalam Pembangunan Jalan Di Negeri Hila, Maluku Tengah - Ony Frengky Rumihin (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Road infrastructure development is a crucial step in enhancing connectivity and economic growth in a region. However, often, road construction can have negative impacts on the environment if not managed properly. The preparation of an Environmental Impact Analysis (AMDAL) is one approach that can minimize these negative impacts and maintain a balance between development and the environment. This community service aims to increase the understanding of the community in Negeri Hila, Central Maluku, about the importance of AMDAL in road development. Through various participatory and educational activities, the service team aims to provide information about the AMDAL process, its benefits in road development, and the importance of community involvement in environmental impact assessments. The methods used in this community service include interactive workshops, group discussions, and the distribution of educational materials on AMDAL. Additionally, the service team collaborates with relevant institutions to provide training to local government staff on the AMDAL process to enhance understanding and effective implementation. The results of this community service are expected to create awareness among the community about the importance of AMDAL in road development and their active role in decision-making related to environmental impacts. Furthermore, it is hoped that this initiative will encourage the broader implementation of AMDAL in development projects in the region to achieve sustainable and highly supportive environments.